(untitled) (Mustansiria Dental Journal, 2023)
Purpose: This study evaluated the effect of different polyethylene fibers positions on fracture resistance of endodontic treated premolars. Materials & Method: - 40 maxillary upper first premolars had been randomly divided in to 4 groups; (n=10). Except for control group, MOD cavity preparation with no steps were done within groups. After endodontic treatment and adhesive step and band application teeth restored with different techniques as follows: B-incremental with G- aenial posterior micro hybrid composite, C-circumferential Ribbond application (wallpapering) with incremental layering, D- bulkfill technique with ribbond reinforcement . Fracture test was measured using LARYEE device ( a computer controlled universal testing machine, China). Statistical analysis was done by One way ANOVA then LSD test to evaluate significance among groups. Results: The highest mean of fracture resistance in restored groups was recorded with group C (885 N) (wallpapering technique); while group D showed the lowest fracture resistance mean (678 N). Conclusion: positioning of polyethylene fibers circumferentially can enhance the fracture strength of endodontic treated teeth.